Attitudes to corruption amongst Russian police officers and trainees - Beck, Adrian (Crime, law and social change, 2002)
The police are perceived by overseas agencies to play a key role in thedevelopment of democratic states. In the Russian Federation, the promotion of trust between the police and the public has been hampered by the fact that police are perceived by the public, and reported by the media, to be open to using their positions at work to obtain money, goods or services. Survey research about beliefs and values concerning corruption was conductedamongst students and serving officers attending a police institute, whichprovides the most promising Russian police recruits with a four-year higher education leading to the rank of ``officer''. From these ranks will come those police who are likely in future to shape both policy and institutional values. The data provided evidence that ``fast-streamed'' police recruits think that corruption is often justifiable and/or morally acceptable underparticular circumstances, or for particular goals.